Knowledge management system quality:a survey of knowledge management system quality dimensions - A. Jabar, Marzanah; Alnatsha, Abdallah S. M. (IEEE, 2014)
The knowledge management systems are becoming more complex and diverse as a result of advances in information technology. Nowadays, users demanding for more accurate and reliable KMS systems increases the awareness and need of KMS quality. To enhance KMS quality the quality dimensions should be identified first. This paper focuses on investigating the quality dimensions of related KMS work namely: software quality dimensions, data quality dimensions, information quality dimensions and knowledge systems quality dimensions. The extracted quality dimensions will be proposed as the basis of KMS quality dimensions that will be mapped with KM processes to produce the KMS quality framework.